1995
DOI: 10.1007/bf01961846
|View full text |Cite
|
Sign up to set email alerts
|

Bladder dysfunction after repeat laparoscopic uterine nerve ablation (LUNA)

Abstract: Abstract:The authors report a case of voiding dysfunction with reduced sensation and arefiexia 13 months after a repeat LUNA due to pelvic nerve injury. Anatomic distortion and increased vascularity were likely contributing factors. Repeat procedures may expose patients to a risk of such injury due to anatomic distortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It was concluded that there was insufficient evidence to recommend the routine use of LUNA in the management of chronic pelvic pain, but suggested there may be a difference in response between women with endometriosis and those with chronic pelvic pain in the absence of endometriosis. There have been isolated case reports of uterine prolapse 13,14 and bladder dysfunction 15 following LUNA, although the complication rate attributable directly to LUNA appears to be extremely low 12 . Other adverse effects of neuroablation, such as haematoma formation, constipation and subsequent painless labour, appear to be more associated with presacral neurectomy (PSN) than LUNA.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that there was insufficient evidence to recommend the routine use of LUNA in the management of chronic pelvic pain, but suggested there may be a difference in response between women with endometriosis and those with chronic pelvic pain in the absence of endometriosis. There have been isolated case reports of uterine prolapse 13,14 and bladder dysfunction 15 following LUNA, although the complication rate attributable directly to LUNA appears to be extremely low 12 . Other adverse effects of neuroablation, such as haematoma formation, constipation and subsequent painless labour, appear to be more associated with presacral neurectomy (PSN) than LUNA.…”
Section: Introductionmentioning
confidence: 99%
“…A long‐term study showed that success rates declined rapidly over time from 72% in the first year to 39% in the fourth for LUNA. 23 Others have suggested a possible risk of anatomical distortion such as uterine prolapse 24,25 and bladder dysfunction 26 following LUNA. There is also the concern regarding the effects of interruption of the pelvic nerves to the uterine muscles in subsequent pregnancies, such as painless labour.…”
Section: Introductionmentioning
confidence: 99%
“…In addition both operations only partially interrupt some of the cervical sensory nerve fibers in the pelvic area; therefore dysmenorrhea associated with additional pelvic pathology may not always benefit from this type of surgery. Other concerns are the risk of anatomical distortion such as uterine prolapse and bladder dysfunction (40, 41). There is also concern regarding the effects of interruption of the pelvic nerves to the uterine muscles in subsequent pregnancies, including an effect like painless labor.…”
Section: Resultsmentioning
confidence: 99%